Universalising the particular: strategic framing in immigrant cross-border activism. Issue 7 (18th May 2020) - McClean, Angela Y.
ABSTRACT: Existing literature on transnational migration suggests that immigrants' participation in political cross-border activism is particularistic, meaning it is defined by national, racial, or ethnic connections to their ancestral homeland. However, I argue that migrant cross-border activists seeking support from the host country strategically avoid using particularistic rhetoric, and instead opt to use universalistic frames to better resonate with audiences in the host society and immigrant community. Striking this broader resonance, in turn, helps to not only justify the movement but also expand it in the host society. I elaborate these arguments using a case study of the World War II 'comfort women' movement led by Korean-Americans. Textual analysis of Korean-American newspaper articles and interviews with Korean-American activists show that universalistic frames have predominated, and that they were used by core groups of activists to appeal to the American mainstream.